Comprehensive Face Analysis and Mathematical Calculations for Enhanced Data Interpretation and Predictive Modeling (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This paper explores the integration of eye-tracking technology with computer vision to enhance human-computer interaction. In a world where precision and efficiency are vital, it examines how eye-tracking can revolutionize mouse cursor control with unmatched accuracy. The research focuses on developing and implementing an innovative eye-tracking-based mouse control system, utilizing advanced algorithms and data processing techniques to translate eye movements into precise cursor actions. This technology offers significant benefits, particularly for improving accessibility for individuals with motor disabilities, enriching gaming experiences, and boosting productivity in professional environments. The seminar provides a comprehensive overview of the current capabilities and future possibilities of eye-tracking technology in mouse motion control, highlighting its transformative potential and setting the stage for future innovations in visual precision for human-computer interaction.